Systemic toxicity to local anesthesia in an infant undergoing circumcision - Ozer, Ayse Belin; Erhan, Omer Lutfi (Kare Publ, 2014)
A circumcision was planned for a four-month-old infant under local anesthesia. After the application of lidocaine, the infant stopped crying, and then generalized tonic-clonic convulsions and a diffuse erythematous rash developed. The patient was immediately monitored, ventilation was provided, and 1 mg midazolam was given intramuscularly. After insertion of a cannula, sodium thiopental 50 mg was given intravenously, the patient's convulsions were controlled, and endotracheal intubation was performed. The patient was extubated 30 minutes later. However, the patient was re-intubated due to his noisy breathing, and 10 mg prednisolone was given intravenously due to mild edema seen in the larynx during endotracheal intubation. Two hours after the second intubation, the patient started to breath spontaneously and opened his eyes; he was extubated and transferred to the intensive care unit. Two days later the patient was discharged. Systemic toxicity to the local anesthesia was considered in this patient. All precautions need to be considered during the application of local anesthesia in pediatric patients, including proper indication, monitoring of the patient in the preoperative period, establishment of venous access, and readiness to apply cardiopulmonary resuscitation in the event of local anesthetic toxicity. The maximum dose of local anesthesia should be considered and it should be diluted during application.
Keywords: Convulsion; infant; lidocaine; local anesthetic toxicity